Implementation Of Accounting Information Systems By Small And Medium Enterprises In Banyumas - Negina Kencono Putri; Siti Maghfiroh (LPPM ISNJ Bengkalis, 2022)
The purpose of this study is to identify a map of the SME sector in the region and the understanding/appreciation of the owner or manager of SMEs towards accounting information systems. Then identify the needs of the SMEs sector in the regions related to the financial information system. Furthermore, identify all activities related to SME financing in each regional sector. This study is a survey research data collection via questionnaires. The sample study was 25 SMEs sector in the regions that are already exporting or potentially exporting in the region of Indonesia. The data were analyzed using the descriptive analysis method. The results of this study indicate that the SME sector in the regions does not yet utilize the accounting information system well; even some SMEs have not done the appropriate financial reporting standards requiring comprehensive financial information system development. With comprehensive financial information systems, SME management can generate financial statements following applicable regulations and standards and disseminate such statements more easily.